Quality Analysis of Biobriquettes Combination Ratio of Oil palm Frond and Water Hyacinth Waste with Durian Seed Flour Adhesive - Mersi Suriani Sinaga; Rondang Tambun; Melvan Tjung; Dadi Oslar Sitinjak (Journal of Chemical Engineering Research Progress, 2025)
This study investigates the production of biobriquettes from a mixture of oil palm frond waste and water hyacinth using durian seed flour as a sustainable adhesive. Biobriquettes were fabricated with varying mass ratios of oil palm frond to water hyacinth (25:75, 50:50, and 75:25) and adhesive concentrations (5%, 10%, 15%, and 20%). Durian seed flour was selected for its starch content, offering an eco-friendly alternative to conventional adhesive like tapioca flour without competing with food resources. Slow primary carbonization (pyrolysis) was employed as the fabrication method. The produced biobriquettes were analyzed for moisture content, ash content, volatile matter, fixed carbon, and calorific value. The optimal formulation was identified at a 75:25 ratio of oil palm frond to water hyacinth with 15% durian seed flour adhesive, yielding a moisture content of 5.91%, volatile matter of 13.97%, ash content of 3.05%, fixed carbon content of 77.07%, and a calorific value of 6,400.78 cal/g. These results demonstrate the potential of durian seed flour as an effective adhesive and highlight the feasibility of utilizing agricultural and invasive biomass wastes to produce high-quality, sustainable biobriquettes. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).